Biostratigraphy of Limestone based on Large Foraminifera in the Donggala Region, Central Sulawesi: Biostratigrafi Batugamping Berdasarkan Kandungan Foraminifera Besar di Daerah Donggala, Sulawesi Tengah - Nurhikmah Supardi; Savira Aulia Rahmawati (JURNAL GEOCELEBES, 2022)
The Sulawesi Molasa Formation is mostly composed of clastic and carbonate sediments which are widely distributed on the island of Sulawesi. Research on the Sulawesi Molasa Formation has been carried out by several researchers. However, there has been no detailed research on limestone biostratigraphy in the Donggala area, so it is very important to do it. This study aims to analyze the age and depositional environment of the Sulawesi Molasa Formation limestone based on the content of large foraminifera. The method used in data collection is measuring section. Field data collection was carried out by stratigraphic measurements including lithology identification, thickness and rock sampling. Laboratory observations were carried out using a polarizing microscope to observe a thin section of rock to determine the species of large foraminifera, their mineral and organic compositions. From the results of field observations found four types of lithology, namely wackestone, packstone, grainstone and floatstone. Based on the observation of large foraminifera fossils in a thin section of limestone in the study area, there are 24 species of large foraminifera identified. Among them, there are four index fossils, namely Miogypsinoides dehaarti (van der Vlerk), Paleomiogypsina bononensis (Matsumaru), Miogypsina sp, (Vaughan), Paleomiogypsina sp, and Miogypsinella sp, (Aquitanian). Based on age withdrawal and description of large foraminifera fossils, it is known that the limestones of the study area are Early Miocene-Middle Miocene age with the depositional environment in the lagoon zone to the forereef shelf